Reintegrasi Ekonomi sebagai Konsep Pembaharuan Hukum Pemasyarakatan Indonesia - Musakkir Musakkir; Andi Armansyah Akbar; Sri Aero Aurora (Jurnal Ilmiah Kebijakan Hukum, 2023)
Economic Reintegration as A Concept Of Indonesia Correctional Law Reform Correctional has become an integral subsystem of the integrated criminal justice system organized by the government as part of the law enforcement process in the context of service, coaching and guidance that will lead to social reintegration. However, until now, there is no consensus on the most effective pattern in helping social reintegration in reducing recidivism rates. Occupation and recidivism rates have a cybernetic relationship, this can be seen in several studies. Therefore, it is necessary to have the proper concept of correctional law reform in terms of concepts and goals that were previously only oriented toward social reintegration into social and economic reintegration. This economic reintegration can be realized through an economical correctional law system, which is in terms of legal substance, that constructing correctional law provisions based on legal and economic principles, in terms of legal structure, that is adding vocational education programs and work internships in coaching and guidance in self-reliance, optimizing the role of cooperatives, MSMEs, and correctional care community groups.